Correction: Proteomic Profiling Reveals Specific Molecular Hallmarks of the Pig Claustrum - Andrea Pirone; Federica Ciregia; Giulia Lazzarini; Vincenzo Miragliotta; Maurizio Ronci; Mariachiara Zuccarini; Lorenzo Zallocco; Daniela Beghelli; Maria Rosa Mazzoni; Antonio Lucacchini; Laura Giusti (Molecular Neurobiology, 2024)

Proteomic Profiling Reveals Specific Molecular Hallmarks of the Pig Claustrum - Andrea Pirone; Federica Ciregia; Giulia Lazzarini; Vincenzo Miragliotta; Maurizio Ronci; Mariachiara Zuccarini; Lorenzo Zallocco; Daniela Beghelli; Maria Rosa Mazzoni; Antonio Lucacchini; Laura Giusti (Molecular Neurobiology, 2023)
The present study, employing a comparative proteomic approach, analyzes the protein profile of pig claustrum (CLA), putamen (PU), and insula (IN). Pig brain is an interesting model whose key translational features are its similarities with cortical and subcortical structures of human brain. A greater difference in protein spot expression was observed in CLA vs PU as compared to CLA vs IN. The deregulated proteins identified in CLA resulted to be deeply implicated in neurodegenerative (i.e., sirtuin 2, protein disulfide-isomerase 3, transketolase) and psychiatric (i.e., copine 3 and myelin basic protein) disorders in humans. Metascape analysis of differentially expressed proteins in CLA vs PU comparison suggested activation of the α-synuclein pathway and L1 recycling pathway corroborating the involvement of these anatomical structures in neurodegenerative diseases. The expression of calcium/calmodulin-dependent protein kinase and dihydropyrimidinase like 2, which are linked to these pathways, was validated using western blot analysis. Moreover, the protein data set of CLA vs PU comparison was analyzed by Ingenuity Pathways Analysis to obtain a prediction of most significant canonical pathways, upstream regulators, human diseases, and biological functions. Interestingly, inhibition of presenilin 1 (PSEN1) upstream regulator and activation of endocannabinoid neuronal synapse pathway were observed. In conclusion, this is the first study presenting an extensive proteomic analysis of pig CLA in comparison with adjacent areas, IN and PUT. These results reinforce the common origin of CLA and IN and suggest an interesting involvement of CLA in endocannabinoid circuitry, neurodegenerative, and psychiatric disorders in humans.

Chemical composition and biological activities of the essential oil from Pulicaria undulata (L.) C. A. Mey. growing wild in Egypt - Ahmed M. Mustafa; Samih I. Eldahmy; Giovanni Caprioli; Massimo Bramucci; Luana Quassinti; Giulio Lupidi; Daniela Beghelli; Sauro Vittori; Filippo Maggi (Natural Product Research, 2020)